Bilirubin-albumin binding capacity in term and preterm infants - M. Basalamah; Achmad Surjono (Paediatrica Indonesiana, 2007)
Background The risk of kernicterus remains a problem injaundiced newborn especially in low birth weight infants.Kernicterus can develop at low bilirubin levels. Bilirubin-albuminbinding plays an important role in its pathogenesis. Bilirubinalbumin binding concentration can also be used as the cut-offpoint in the administration of phototeraphy.Objective To determine the pattern of albumin bindingconcentration in serum model in vitro and in serum of prematureand term newborn infants from cord blood sample.Methods This study was conducted in Installation of Maternal-Perinatal Dr. Sardjito Hospital from August-September 2004.Blood cord samples from 20 term and 17 preterm infants wereanalysed. Total bilirubin was measured spectrophotometrically andunbound bilirubin concentration was determined by horseradishperoxidase oxidation using UB-analyzer apparatus micromethod.Student t test and linear regression analysis were performed.Results Bilirubin-albumin binding capacity of term infants showeda statistically significant difference compared to that of prematureinfants (18.9Â±2.1 mg/dl vs 10.2Â±3.6 mg/dl, P<0.001). This cut-off level approximately reflected a value of unbound bilirubin of1 mg/dl in term and 0.5 mg/dl in premature infants.Conclusions There is a different pattern of bilirubin-albuminbinding capacity between term and preterm infants which is higherin term infants. Bilirubin level of 19 mg/dl and 10 mg/dl in termand preterm newborn, respectively, can be used as cut-off pointto perform more aggressive intervention, such as phototeraphy,and to lower the risk of kernicterus.